Employees' Knowledge and Skills on Work Productivity at the Manpower Department - Sarthek Nishu; Akash Lalrinzuala (Journal La Bisecoman, 2021)
The purpose of this research is to evaluate the impact of improving staff knowledge and skills on job productivity. This study employs a descriptive quantitative approach. The findings of this research show that increasing knowledge has a positive and significant impact on job productivity, with tcount = 4.236 > ttable = 1.674 and a significance level of 0.000 0.05. While the employee competence variable has a positive and substantial impact on job production (tcount = 3.143 > ttable = 1.674 with a significant 0.003 0.05)